Transjugular Intrahepatic Portosystemic Shunt (TIPS) Extension for Transhepatic Mesocaval Shunt Creation: A Case Series for Treating Refractory Upper Gastrointestinal Bleeding in Patients with Chronic Portal Vein Thrombosis - Patidar, Yashwant; Babbar, Sushant; Mukund, Amar; Sarin, Shiv Kumar (Indian Journal of Radiology and Imaging, 2023)
Transjugular intrahepatic portosystemic shunt (TIPS) is known to benefit patients with decompensated liver disease by alleviating portal pressure. However, TIPS creation is technically difficult and challenging to perform in patients with chronic portal vein thrombosis (PVT) (4,5). Multiple endovascular techniques for portal vein recanalization with or without creating portosystemic shunt are available to decompress and alleviate portal hypertension in patients with PVT. In this case series, we represent TIPS extension to create an endovascular mesocaval shunt for the treatment of refractory upper gastrointestinal bleeding.
Keywords: mesocaval shunt; PVR TIPS; chronic PVT; portal hypertension